Demographic parameters in the population of dogs and cats in human settlements of the district of Ventanilla, Callao-Peru - Rendón H., Diana (2018)
The study aimed to determine demographic indicators of the population of domestic dogs and cats with owner in human settlements in the district of Ventanilla, Callao (Peru). A cluster sampling was performed to select the population groups and a stratified and systematic sampling was used to select the dwellings. The information was collected through a survey. The demographic characteristics of dogs and cats, and the relation dog:person and cat:person was calculated. In total, 61.9 and 40.0% of the houses owned dogs and cats, respectively. The number of pets per household was 1.8 in both species. The number of offspring in dogs was 4.3 and in cats was 3.1. The estimated survival rate was 56.2 ± 3.0% for puppies and 66.4 ± 3.9% for kittens. The estimated life expectancy was 4.21 ± 0.44 years in dogs and 2.64 ± 0.46 years in cats. It was estimated that there were 1 dog per 3.98 persons and 1 cat per 5.34 persons. Twenty-three percent of respondents said they maintained stray dogs outside homes. It is expected that the information provided will serve health authorities to plan population control programs and responsible pet ownership in this population.